(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
The aim of the research is to highlight the impact of the use of enterprise management techniques on enterprise development by applying to private sector companies in the eastern region of Saudi Arabia by clarifying the dimensions of enterprise development, as well as to reveal the impact of project management techniques on enterprise development in its dimensions (project scheduling, project resources, project cost, project risks, project quality). The researcher has relied on the analytical descriptive approach to achieve the objectives of the study. The identification was used as an information-gathering tool. This research was applied to a study community consisting of workers from private sector companies in the eastern region within Saudi Arabia. (SPSS). This research has yielded a series of important findings, the most significant of which is that there is a statistically significant effect between the techniques used in project management (as a separate variable) and enterprise development (as a follow-up variable) within private sector companies in the eastern region of Saudi Arabia. There is a statistically significant effect between the techniques used in project management (as a separate variable) and the scheduling of projects (as a first dimension of enterprise development) (as a follow-up variable) within private sector companies in the eastern region of Saudi Arabia. The researcher recommended the need for senior management to develop skills through continuous training in project management. There is a need for agreement between senior leadership in projects and departments on the determinants of strategic plan development. Resource management depends on the efficiency and effectiveness of project planning.